2014
DOI: 10.1080/21683565.2013.878429
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Biological and Cultural Practices Can Reduce Crop Rotation Period of Organic Strawberries

Abstract: A team of researchers conducted a replicated on-farm experiment

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 31 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…In contrast, the few growers we interviewed who used more diversified farming methods to control pathogens were much more satisfied with the results. Along with growers, field trial researchers have found effective pest suppression with rotations of plants with biofumigation properties, such as brassicas, along with cover crops and composting, especially in 3to 4-year cycles (Hodson and Lewis 2016;Lloyd 2015;Muramoto et al 2014). The problem, however, with any nonchemical alternative that requires growers to rotate strawberries with a lower value or no-value crop, especially over several years, is that lease costs are generally based on an expectation that strawberries will be grown on an annual basis, not be a minor crop in an integrated diversified system.…”
Section: Land Value Is Obstacle To Changementioning
confidence: 99%
“…In contrast, the few growers we interviewed who used more diversified farming methods to control pathogens were much more satisfied with the results. Along with growers, field trial researchers have found effective pest suppression with rotations of plants with biofumigation properties, such as brassicas, along with cover crops and composting, especially in 3to 4-year cycles (Hodson and Lewis 2016;Lloyd 2015;Muramoto et al 2014). The problem, however, with any nonchemical alternative that requires growers to rotate strawberries with a lower value or no-value crop, especially over several years, is that lease costs are generally based on an expectation that strawberries will be grown on an annual basis, not be a minor crop in an integrated diversified system.…”
Section: Land Value Is Obstacle To Changementioning
confidence: 99%
“…This disease can spread rapidly in the field, especially under favorable environmental conditions, making it challenging to control [ 18 ]. Farmers typically use a combination of cultural practices, such as crop rotation, sanitation, resistant cultivars, and fungicides [ 19 ]. Among these management practices, chemical fungicides are commonly used for managing this disease, but their effectiveness is challenged by the increasing fungicide resistance of the pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Crop rotations are commonly used to suppress various diseases and, in the case of strawberries, rotations with V. dahliae non-host crops like broccoli can reduce the severity of Verticillium wilt (Muramoto et al 2014;Subbarao et al 2007). Unfortunately, more profitable rotation crops, like lettuce, are hosts and can increase the severity of Verticillium wilt in subsequent strawberry crops.…”
mentioning
confidence: 99%